Aminolevulinic acid dendrimers in photodynamic treatment of cancer and atheromatous disease1. Issue 9 (26th September 2015) - Rodriguez, L.; Vallecorsa, P.; Battah, S.; Di Venosa, G.; Calvo, G.; Mamone, L.; Sáenz, D.; Gonzalez, M. C.; Batlle, A.; MacRobert, A. J.; Casas, A.
<x xml:space="preserve">Abstract</x> ALA dendrimers are taken up by caveolae-mediated endocytosis in macrophages. Intracellular ALA release gives rise to PpIX synthesis and subsequent photosensitization of key cells in atheromas and tumour diseases.